2020
DOI: 10.1016/j.omtn.2020.05.022
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Overexpression of MicroRNA-340-5p Inhibits Pulmonary Arterial Hypertension Induced by APE by Downregulating IL-1β and IL-6

Abstract: Pulmonary arterial hypertension (PAH) is a fatal cardiovascular disease that could eventually result in right ventricular failure. Recently, the roles of microRNAs (miRNAs) in PAH have been highlighted. The present study aims to investigate the effects of miRNA (miR)-340-5p on PAH induced by acute pulmonary embolism (APE) and the underlying mechanisms. miR-340-5p was lowly expressed, whereas interleukin 1β (IL-1β) and IL-6 were highly expressed in plasma of APE-PAH patients as compared to normal human plasma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…In ECs, the miR-17~92 cluster and miR-27a are upregulated but miR-21, miR-424 and miR-503 are downregulated. miR-340-5p was shown to be downregulated after acute pulmonary embolism and its overexpression in vivo prevented the development of PAH in a rat model of embolism through direct targeting of both interleukin-6 (IL-6) and interleukin-1β (IL-1β) and subsequent activation of nuclear factor κβ (NF-κβ) in PASCMs [ 181 ]. miR-138-5p is upregulated in PASMCs from PAH patients as well from rats subjected to MCT-induced PAH and its inhibition restores KCNK3 and Solute carrier family 45-member 3 ( SLC45A3 ) expression and ameliorates PAH and RV function [ 182 ].…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…In ECs, the miR-17~92 cluster and miR-27a are upregulated but miR-21, miR-424 and miR-503 are downregulated. miR-340-5p was shown to be downregulated after acute pulmonary embolism and its overexpression in vivo prevented the development of PAH in a rat model of embolism through direct targeting of both interleukin-6 (IL-6) and interleukin-1β (IL-1β) and subsequent activation of nuclear factor κβ (NF-κβ) in PASCMs [ 181 ]. miR-138-5p is upregulated in PASMCs from PAH patients as well from rats subjected to MCT-induced PAH and its inhibition restores KCNK3 and Solute carrier family 45-member 3 ( SLC45A3 ) expression and ameliorates PAH and RV function [ 182 ].…”
Section: Epigenetic Regulationmentioning
confidence: 99%
“…In the dual-luciferase reporter assay regarding miR-340-5p, IL-1β and IL-6, both pro-inflammatory targets were confirmed to be downregulated by miR-340-5p directly, revealing a synergistic anti-inflammation effect of miR-340-5p. Therefore, miR-340-5p might be a promising therapeutic target as an anti-inflammatory agent ( Ou et al, 2020 ).…”
Section: Mirnas Are Potential Novel Therapeutic Targets For Pementioning
confidence: 99%
“…31 Enhanced miR-340-5p expression can inhibit the inflammatory response of pulmonary artery smooth muscle cells by declining the levels of IL-1β and IL-6. 18 It was suggested that overexpression of miR-340-5p attenuated the damage of Mtb to A549 cells by mitigating inflammatory responses and reducing Mtb survival. Subsequently, the target genes of miR-340-5p were predicted by bioinformatics website.…”
Section: Discussionmentioning
confidence: 99%
“…miR-340-5p Targets TMED7 to Mediate the NF-κB Pathway miR-340-5p can inhibit inflammation in pulmonary hypertension, neuroinflammation and heart injury by inhibiting the activation of NF-κB, [16][17][18] while TMED7 is a cisrelated gene of NF-κB. 19 Therefore, we speculated that miR-340-5p can reduce the Mtb infection-induced inflammatory responses by inhibiting TMED7 and NF-κB pathway.…”
Section: Overexpression Of Tmed7 Attenuates the Protective Effect Of Mir-340-5p Mimic On Mtb-infected A549 Cellsmentioning
confidence: 99%